Current Advances on the Important Roles of Enhancer RNAs in Gene Regulation and Cancer. (22nd May 2018) - Liu, Yuhan; Ding, Mengting; Gao, Qunjun; He, Anbang; Liu, Yuchen; Mei, Hongbing
Abstract : Revealing the gene regulation networks governing cancer initiation and development is necessary while it remains uncompleted. In recent years, enhancers have been reported to be widely transcribed, resulting in the generation of enhancer RNAs (eRNAs). Previous studies have reported that eRNAs are a subclass of long noncoding RNAs (lncRNAs), which play a critical role in gene regulation and cancer development. These eRNAs can promote enhancer-promoter (E-P) looping formation by binding to other protein factors or propel expression of downstream protein-coding gene. In this review, we have focused on the characteristics of eRNAs and illustrated the biological function and potential mechanism of eRNAs in regulating gene expression and cancer development.